1987
DOI: 10.1021/bi00389a028
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, structural, and spectroscopic indentification of geminate states of myoglobin: a ligand binding site on the reaction pathway

Abstract: Elementary steps or geminate states in the reaction of gaseous ligands with transport proteins delineate the trajectory of the ligand and its rebinding to the heme. By use of kinetic studies of the 765-nm optical "conformation" band, three geminate states were identified for temperatures less than approximately 100 K. MbCO, which is accumulated by photolysis between 1.2 and approximately 10 K, was characterized by our previous optical and X-ray absorption studies [Chance, B., Fischetti, R., & Powers, L. (1983)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…In a pioneering experiment, Mills and co-workers probed the reversible photodissociation of a CO group from carboxymioglobin via TR-XANES at the Fe K-edge [140,[234][235][236]. Similar studies on related systems were reported by Clozza et al [237] and by Chance and co-workers [141,[238][239][240]. In addition, Chen et al investigated the lightdriven redox processes in an Fe-Zn diporphyrin integrated in a modified haem protein [241].…”
Section: (Py) 2 ] 2+mentioning
confidence: 84%
“…In a pioneering experiment, Mills and co-workers probed the reversible photodissociation of a CO group from carboxymioglobin via TR-XANES at the Fe K-edge [140,[234][235][236]. Similar studies on related systems were reported by Clozza et al [237] and by Chance and co-workers [141,[238][239][240]. In addition, Chen et al investigated the lightdriven redox processes in an Fe-Zn diporphyrin integrated in a modified haem protein [241].…”
Section: (Py) 2 ] 2+mentioning
confidence: 84%
“…Whereas the time scale for the protein relaxation is highly dependent on solution conditions to the extent that they can be greatly slowed by enhancing the solution viscosity, the rapid motion of the iron appears insensitive to environmental factors. There is Raman evidence that the iron displacement can be inhibited only at liquid helium temperatures (18,20,21,48).…”
Section: Discussionmentioning
confidence: 99%
“…To an extent, the inverse temperature effect is an inverse viscosity effect in which the overall recombination process gets slower with decreasing viscocity The origin of both the onset of the new phases and the related inverse temperature/viscosity effect has been vigorously explored and debated. The central focus was whether these processes were being driven by barrier-raising conformational relaxations (Agmon and Hopfield, 1983;Ahmed et al, 1991;Ansari et al, 1992;Abadan et al, 1995) or by increased access of the dissociated ligand to slow rebinding docking sites (Powers et al, 1987; within the protein matrix by the dissociated CO. Initially, the spectroscopic and theoretical work favored the barrier raising relaxation model.…”
Section: Recombination Studies At Cryogenic Temperaturesmentioning
confidence: 99%